The Physical Characteristics of Handmade soap with Plant-Based Additives - Hosni, Hazim; Mohd Rus, Anika Zafiah (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The application of soap is very significant in daily lives to eliminate any dirt which cannot be completely remove by water alone. The production of soap is mainly consisting of harmful chemical substance which can deliver bad effect on human skin for long term use. Moreover, the commercial soap focuses on increasing the mass production of the soap which can reduce the physical characteristics of the soap such as hardness, pH value and resistance of dissolvement. Accordingly, there is a need for improved physical characteristics of the soap. The objective of this research is to use virgin cooking oil and different types of herbs in soap making process and to identify the physical characteristics of the soap which is made using virgin cooking oils and herbs additives. This study also needs to prepare simple and attractive information using brochure for distribution among small and medium enterprise (SME) for soap making process. The production of handmade soap involves virgin cooking oil, lye, and plant-based additives by using cold process method. Three types of tests were conducted to determine physical characteristics of handmade soap with plant-based additives which is Scratch Resistance test, pH test, and Swelling test. The scratch resistance test was carried out by using pencil hardness method to ascertain the hardness, pH test for pH value, and swelling test for resistance of dissolvement in four different solutions including oil, vinegar, salt and sugar. The results indicates that the handmade soap with plant-based additives produced acquire strong hardness and a safe range of pH value 9 to 10. To conclude, this study revealed that handmade soap with plant-based additives significantly enhance the physical characteristics of the soap and can be improve for next research with some recommendations